(untitled) - Terrance Keys (New York, 2000)
The book is designed to assist anyone who desire to teach others by covering the skills that are necessary for success in this profession. Improving your teaching or training skills can be accomplished in a variety ways. Feedback from colleagues or students provides a trainer with invaluable feedback, yet being proactive about your training skills is critical to becoming a good or even better trainer. This can be accomplished by understanding and implementing the training standards discussed in this book.